Biofouling Community Structure in a Tropical Estuary of Goa on the West Coast of India - Dattesh V Desai; Venkat Krishnamurthy; Arga Chandrashekar Anil (ASEAN Journal on Science and Technology for Development, 2018)
Biofouling community structure was studied in a tropical monsoon-influenced Mandovi estuary in Goa, west coast of India. Monthly, seasonal and yearly observations on biofouling on polyvinyl chloride (PVC) panels immersed at subsurface water level were recorded and photographed from May 2012 to September 2013. The barnacle Balanus amphitrite was the dominant fouling organism followed by calcareous polychaetes. The settlement and recruitment of barnacles took place year-round, with the exception of July 2012 and June 2013 (monsoon months). However, their peak abundance was observed during the later months of monsoon (August and September). Polychaetes were dominant during late post-monsoon and pre-monsoon months (December 2012 to April 2013). Silt and slime were observed throughout the observation period. Comparing the fouling pressure of barnacles in the two monsoon seasons (2012 and 2013), fouling was more intense during the monsoon of 2013, indicating an inter-annual variation in the fouling community.